Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/we.2641
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of offshore wind variability

Abstract: Using the 40‐year hourly gridded ERA5 reanalysis, we study the offshore patterns of wind variability using the probability density function (PDF) and the power spectral density (PSD). To summarize wind variability, we compute the Weibull parameters from the PDF and the PSD for six spectral bands: interannual, annual, multimonth, storm, diurnal, and semidiurnal. We characterize the storm spectral peak using a Gaussian function in normallog10 frequency space. These parameters are plotted along two pole‐to‐pole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Studies of seasonal‐to‐interannual variability in hub‐height wind speed (and thus wind energy) have demonstrated its strong linkage with midlatitude synoptic‐scale weather (i.e., high‐ and low‐pressure systems). For example, Millstein et al 1 identified synoptic‐scale patterns corresponding to periods of above‐ and below‐normal wind speed in central and southern California, USA; Coburn 2 showed that synoptic‐scale weather patterns have a significant impact on total energy output at wind energy sites in a midcontinental region of the USA, and West and Smith 3 found that synoptic‐scale variability was the dominant driver of offshore wind speed variability in the midlatitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of seasonal‐to‐interannual variability in hub‐height wind speed (and thus wind energy) have demonstrated its strong linkage with midlatitude synoptic‐scale weather (i.e., high‐ and low‐pressure systems). For example, Millstein et al 1 identified synoptic‐scale patterns corresponding to periods of above‐ and below‐normal wind speed in central and southern California, USA; Coburn 2 showed that synoptic‐scale weather patterns have a significant impact on total energy output at wind energy sites in a midcontinental region of the USA, and West and Smith 3 found that synoptic‐scale variability was the dominant driver of offshore wind speed variability in the midlatitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Among other aspects, seasonal variations are particularly important in this case, as the seasonal demand shows two maxima in winter and summer, and summer demand is expected to increase in the future due to the growing frequency of heat waves [20]. Previous studies have analysed temporal variability of the wind resource at different time scales [15,[21][22][23]. Spatial complementarity among the different installation sites can be used to smooth out the temporal variability of the combined power supply [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Two numerical methods can be applied for these purposes; in the first method, defined as the shore protection manual (SPM) method, both significant Water 2022, 14, 843 2 of 13 wave height H m 0 (m) and peak wave period T p (s) can be obtained by employing wind data [12][13][14][15][16][17][18]. The second method is the so-called spectral method [19,20]. When wave peak period and height are needed, these parameters are estimated from the so-called wave spectrum, which is obtained from the SPM method.…”
Section: Introductionmentioning
confidence: 99%